2014
DOI: 10.1155/2014/374027
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin Contamination in Sea Mussel Farms from the Italian Southern Adriatic Coast following Cyanobacterial Blooms in an Artificial Reservoir

Abstract: An experimental study was performed in 2009-2010 to investigate the polluting effect of eutrophic inland waters communicating with the sea coast. The study was planned after a heavy and long-lastingPlanktothrix rubescensbloom occurred in the Lake Occhito, an artificial reservoir. The waters of the reservoir flow into the southern Adriatic Sea, near several marine breeding ofMytilus galloprovincialismussels, a typical seafood from the Apulia region (Southern Italy). A monitoring study of water and mussels from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 75 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…MCs from freshwater sources have been detected in near-shore marine systems (Robson and Hamilton, 2003;Miller et al, 2010;Gibble and Kudela, 2014), yet monitoring for the toxin in marine waters and seafood has been limited (De Pace et al, 2014). Our findings provide the first documentation of MC presence in Puget Sound waters and the first to establish a direct relationship outside the laboratory, in the United States, between MC in inland lakes and marine seafood intoxication.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…MCs from freshwater sources have been detected in near-shore marine systems (Robson and Hamilton, 2003;Miller et al, 2010;Gibble and Kudela, 2014), yet monitoring for the toxin in marine waters and seafood has been limited (De Pace et al, 2014). Our findings provide the first documentation of MC presence in Puget Sound waters and the first to establish a direct relationship outside the laboratory, in the United States, between MC in inland lakes and marine seafood intoxication.…”
Section: Discussionmentioning
confidence: 58%
“…4). Other studies have also reported detection of MC in biota even in the absence of MC in surrounding waters (Prepas et al, 1997;Miller et al, 2010;De Pace et al, 2014). Because field-sampling techniques can significantly affect MC detection (Tillmans et al, 2007) our MC measurements in water samples, especially marine waters, should be considered conservative.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Salinity is an important abiotic factor that affects physiological and ecological performance of phytoplankton species, including cyanobacteria (De Pace et al 2014;Teikaki et al 2018;Tonk et al 2007). We focused on the morphological and physiological changes of P. agardhii, a dominant species from a brackish pond that might therefore be pre-adapted to varying salinities (Vergalli 2013).…”
Section: Ecological Implications and Perspectivesmentioning
confidence: 99%
“…those acclimated to high salt concentrations near full seawater, have genes for sucrose synthesis with a suite of general and salt-stress-specific genes and regulatory systems enabling them to cope with changing environments (Tanabe et al 2018;Teikaki et al 2018Teikaki et al , 2019. Earlier studies reported controversial results on cyanobacterial responses and capacity to cope with salt-stress (De Pace et al 2014;Tolar 2012;Tonk et al 2007), even at the intraspecific level (Otsuka et al 1999). While some Microcystis strains resisted 10 g l −1 of NaCl (Orr et al 2004;Tonk et al 2007), others reached their limit at 2 g l −1 , leading the authors to consider this as a strain-specific halotolerance rather than as a species-specific trait (Orr et al 2004).…”
Section: Ecological Implications and Perspectivesmentioning
confidence: 99%